Colton's secret history - Bokal, Jennifer D. (Bokal, Jennifer D. Coltons of Kansas., 2020)
"Returning to her hometown, health investigator Bridgette Colton is reluctantly reunited with old flame Luke Walker. For years, emotionally scarred Bridgette has kept a life-changing secret from Luke. But now their bond lands Bridgette squarely in the path of a terrifying stalker. Losing her heart to Luke again could be a fatal mistake- for them both" --Amazon.